2005
DOI: 10.1016/j.cogbrainres.2005.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Spatial processing in human auditory cortex: The effects of 3D, ITD, and ILD stimulation techniques

Abstract: Here, the perception of auditory spatial information as indexed by behavioral measures is linked to brain dynamics as reflected by the N1m response recorded with whole-head magnetoencephalography (MEG). Broadband noise stimuli with realistic spatial cues corresponding to eight direction angles in the horizontal plane were constructed via custom-made, individualized binaural recordings (BAR) and generic head-related transfer functions (HRTF). For comparison purposes, stimuli with impoverished acoustical cues we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
80
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(110 citation statements)
references
References 52 publications
26
80
1
Order By: Relevance
“…Previous neurophysiological (8,11) and human neuroimaging studies (43,44) generally suggest that nonprimary regions, including PT/posterior STG, process progressively more complex sounds than the primary "core" regions of auditory cortex. These observations are in line with a previous MEG study (45) that systematically compared activations to individual and combined 3D sound features, and showed that ILD alone is not sufficient for producing direction-specific activations at the cortical level. It is also worth noting that in humans, no consistent evidence on ILD-specific fMRI activations in PT/posterior STG exists.…”
Section: Discussionsupporting
confidence: 80%
“…Previous neurophysiological (8,11) and human neuroimaging studies (43,44) generally suggest that nonprimary regions, including PT/posterior STG, process progressively more complex sounds than the primary "core" regions of auditory cortex. These observations are in line with a previous MEG study (45) that systematically compared activations to individual and combined 3D sound features, and showed that ILD alone is not sufficient for producing direction-specific activations at the cortical level. It is also worth noting that in humans, no consistent evidence on ILD-specific fMRI activations in PT/posterior STG exists.…”
Section: Discussionsupporting
confidence: 80%
“…The main effect of the ITDs was significant (P < 0.005). This result is consistent with previous findings Sams et al, 1993;Palomäki et al, 2005). The main effect of the hemispheres on the N1m amplitude was not significant.…”
Section: Estimation Of Localization Performance Related To Itd and Frsupporting
confidence: 83%
“…That is, ipsilaterally localized stimuli produced shorter latencies in the case of right-leading stimuli. This result is consistent with previous findings (McEvoy et al, 1994;Palomäki et al, 2005). Figures 11 show the N1m amplitude as a function of ITD.…”
Section: Wwwintechopencomsupporting
confidence: 82%
“…Whether such functional neuroanatomical gradients nevertheless result in lateralized MLRs remains unclear. Although it is well established that later components of the auditory evoked response-especially the N1-can be lateralized in response to both monaural (Scherg and Von Cramon 1986;Woldorff et al 1999;Hine and Debener 2007;Königs and Gutschalk 2012) and lateralized binaural (McEvoy et al 1993;McEvoy et al 1994;Palomäki et al 2005;Johnson and Hautus 2010;Königs and Gutschalk 2012) stimuli, previous studies examining the MLR are inconclusive. While some have reported balance for monaural stimulation (Peters and Mendel 1974;Scherg and Von Cramon 1986;Kileny et al 1987;Jacobson and Grayson 1988), others have indicated varying degrees of contralateral dominance for the N19 (Woods and Clayworth 1985), the N19-P30 pair (Woods et al 1987), the P30 and P50 , or the P50-N100 pair (Pantev et al 1986), but not for binaural stimuli lateralized by interaural time differences (ITDs) (McEvoy et al 1994).…”
Section: Introductionmentioning
confidence: 76%